IMPLEMENTASI UNDANG-UNDANG OTONOMI KHUSUS DI PROVINSI PAPUA DALAM MEWUJUDKAN KESEJAHTERAAN MASYARAKAT PAPUA - Rosdiana Baso Rante; Ishviati Joenaini Koenti; Endang Sulistyaningsing (Kajian Hasil Penelitian Hukum, 2018)
The province of Papua, which is geographically located on the eastern Indonesia, is the largest province with abundant natural resources. But in reality various policies in centralized governance and development have not fully fulfilled the sense of justice, have not fully enabled the achievement of people welfare, have not fully supported the realization of law enforcement, and have not fully demonstrated respect for human rights in Papua Province, especially the Papuan people. These conditions caused disparities in almost all sectors of life, especially in education, health, economics, culture and social politics, so the Government tried to overcome these problems by providing policies with Special Autonomy in Papua Province. In 2001 the Government legalized the Law No. 21 of 2001, On Special Autonomy for the Papua Province in order to ensure equal distribution of public welfare.Purpose of this study is to find out the implementation of the special autonomy law in the Papua Province in realizing the welfare of the Papuan people. Also to know the obstacle factors faced in the implementation of the special autonomy law in Papua Province. And to find out what solutions are carried out by the Regional Government of the Province of Papua to overcome the problems in the implementation of the special autonomy law.The methods that used in this study are by determine the subject and object of the study, the characteristic of the study, types and sources of data, data collection techniques, and data analysis methods.The results of this study are based on conclusions, namely: 1The implementation of the special autonomy law in the Papua Province has been carried out in accordance with the direction of the Central Government. However, in realizing social welfare for the Papuan people, they still need the struggle and hard work of all elements of people and the local Government in Papua Province; 2 Obstacle factors that came up due to inconsistencies of the Central Government and the Papua Local Government have not been able to apply Special Autonomy maximally; and 3 what the Central Government has to do is to seriously implement this law consistently, avoiding policies that can result in collision of interpretation with the Special Autonomy law. So that the suggestions are 1the Central Government is expected to not carry out policies that collide with special Autonomy laws; 2 The Local Government needs to do two things, namely the realignment of the regional government management system, and the improvement of managerial capacity for regional government officials; and 3 There needs to be a separation between the special autonomy law of Papua Province and West Papua Province.